CONTINUOUS IMPROVEMENT IN TQM - Saeed AlQahtani, Jawaher Abdullah; Turky, Enaas mushabab; AL-Ghamdi, Abdullah Saad AL-Malaise (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The Field of TQM Total quality Management seeks to have all the functions in an organization integrated. IT has been a favorite subject of research specially in the areas of Service and production. The studies aimed at addressing the topic of continual improvement in the sphere of TQM and its applications. Different researchers had their individual approaches and their researches concluded differently. With this paper we attempt to do a comparative analysis of the research work done by various people in the areas of TQM, its aims, principles, models and applications.